Analiza opłacalności wykorzystania gazu ziemnego CNG jako paliwa silnikowego w Polsce - Król, Anna; Lal, Monika (Profitability Analysis of Compressed Natural Gas Application as a Vehicle Fuel in Poland, 2006)
Recently on the Polish market an interesting alternative to so far used vehicle fuels has occurred - Compressed Natural Gas. Its ecological cleanness, safety and many other attractive factors contribute to systematic rise of CNG vehicles number. The aim of this paper is to present economic aspects of CNG application as vehicle fuel in Poland as well as profitability analysis of adapting vehicles to CNG investment. To evaluate investment projects Net Present Value (NPV) method. Internal Rate of Return (IRR) method as well as Sensitivity Analysis have been used.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 277-227